Two multidrug-resistant Proteus mirabilis clones carrying extended spectrum beta-lactamases revealed in a single hospital department by whole genome sequencing - Anna Karpenko; Andrey Shelenkov; Lyudmila Petrova; Vitaly Gusarov; Mikhail Zamyatin; Yulia Mikhaylova; Vasiliy Akimkin (Heliyon)
Proteus mirabilis bacteria is a component of normal intestinal microflora of humans and animals, but can also be found in hospital settings causing urinary tract infections and sepsis. The problem of treating such infections is complicated by multidrug-resistant isolates producing extended spectrum beta-lactamases (ESBL), and the number of ESBL-carrying P. mirabilis strains has significantly increased recently.This study presents a detailed analysis of 12 multidrug-resistant P. mirabilis isolates obtained from the wounds of different patients in one surgical department of a multidisciplinary hospital in Moscow, Russia, using the short- and long-read whole genome sequencing. The isolates under investigation divided into two clusters (clones) C1 and C2 based on their genomic profiles and carried antimicrobial resistance (AMR) genes corresponding well with phenotypic profiles, which was the first case of reporting two different P. mirabilis clones obtained simultaneously from the same specimens at one hospital, to the best of our knowledge. Some genes, including ESBL encoding ones, were specific for either C1 or C2 (aac(6′)-Ib10, ant(2″)-Ia, qnrA1, blaVEB-6 and fosA3, blaCTX -M-65, correspondingly). Additionally, the Salmonella genomic islands 1 were found that differed in composition of multiple antibiotic resistance regions between C1 and C2 groups. CRISPR-Cas system type I-E was revealed only in C2 isolates, while the same set of virulence factors was determined for both P. mirabilis clones.Diversity of all genetic factors found in case of simultaneous existence of two clones collected from the same source at one department indicates high pathogenic potential of P. mirabilis and poses a requirement of proper spreading monitoring. The data obtained will facilitate the understanding of AMR transfer and dynamics within clinical P. mirabilis isolates and contribute to epidemiological surveillance of this pathogen.